EFEKTIVITAS PERATURAN BUPATI NO 69 TAHUN 2018 TENTANG KEBIJAKAN STRATEGI KABUPATEN SAMBAS DALAM PENGELOLAAN SAMPAH RUMAH TANGGA DAN SAMPAH SEJENIS SAMPAH RUMAH TANGGA DI DESA TANJUNG BUGIS TAHUN 2022 - Muhammad Mufizar (Lunggi Journal, 2024)
This study uses a qualitative method and a descriptive approach. Data collection is carried out through interviews, observations, and documentation. Data validity is ensured through prolonged engagement, persistent observation, and verification by research data sources. Data analysis is performed using an inductive model, which includes data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that the effectiveness of Regent Regulation No. 69 of 2018 on Household Waste Management is still low because, although the village government has implemented steps such as sorting, collecting, and transporting waste, management and final processing are not carried out. Internal factors affecting this effectiveness include irregular waste sorting and the lack of a recycling system. External factors include the lack of public awareness about the impact of waste and apathy towards existing regulations.